2015
DOI: 10.1007/s10750-015-2587-4
|View full text |Cite
|
Sign up to set email alerts
|

An Arctic and Subarctic ostracode database: biogeographic and paleoceanographic applications

Abstract: A new Arctic Ostracode Database-2015 (AOD-2015 provides census data for 96 species of benthic marine Ostracoda from 1340 modern surface sediments from the Arctic Ocean and subarctic seas. Ostracoda is a meiofaunal, Crustacea group that secretes a bivalved calcareous (CaCO 3 ) shell commonly preserved in sediments. Arctic and subarctic ostracode species have ecological limits controlled by temperature, salinity, oxygen, sea ice, food, and other habitat-related factors. Unique species ecology, shell chemistry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…In addition, although deep-sea ostracods from normal soft sediments are well studied in the North Atlantic, Nordic seas, and Arctic Ocean (i.e. adjacent regions to the study sites) (Whatley and Coles, 1987;Whatley et al, , 1998Didié and Bauch, 2000;Yasuhara et al, 2009Yasuhara et al, , 2014aAlvarez Zarikian, 2009;Okahashi, 2014, 2015;Gemery et al, 2017), any similar species or genus to Rosaliella svalbardensis has not been reported. Van Harten (1993) suggested that pore clusters in Xylocythere is related to ectosymbiosis of chemoautotrophic bacteria (also see Maddocks, 2005).…”
Section: Rosaliella Svalbardensis As Palaeo-methane Seep Indicatormentioning
confidence: 97%
“…In addition, although deep-sea ostracods from normal soft sediments are well studied in the North Atlantic, Nordic seas, and Arctic Ocean (i.e. adjacent regions to the study sites) (Whatley and Coles, 1987;Whatley et al, , 1998Didié and Bauch, 2000;Yasuhara et al, 2009Yasuhara et al, , 2014aAlvarez Zarikian, 2009;Okahashi, 2014, 2015;Gemery et al, 2017), any similar species or genus to Rosaliella svalbardensis has not been reported. Van Harten (1993) suggested that pore clusters in Xylocythere is related to ectosymbiosis of chemoautotrophic bacteria (also see Maddocks, 2005).…”
Section: Rosaliella Svalbardensis As Palaeo-methane Seep Indicatormentioning
confidence: 97%
“…The primary sources of ostracode taxonomy and ecology were Stepanova (2006), Yasuhara et al (2014), and Gemery et al (2015) and the references therein. The study by Gemery et al (2015) gives the modern depth range and ecological data for 1340 modern surface samples from the Arctic and subarctic seas.…”
Section: Micropaleontologymentioning
confidence: 99%
“…The study by Gemery et al (2015) gives the modern depth range and ecological data for 1340 modern surface samples from the Arctic and subarctic seas. Simple statistical analyses were used to obtain the most reasonable paleodepth estimates from fossil biofacies on the basis of modern ecology and the modern depth ranges of key species.…”
Section: Micropaleontologymentioning
confidence: 99%
See 2 more Smart Citations